2008
DOI: 10.1177/0003319707311536
|View full text |Cite
|
Sign up to set email alerts
|

Carotid and Femoral Atherosclerosis in Chronic Hepatitis C: A 5-Year Follow-Up

Abstract: The objective of this study was to assess the progression of atherosclerosis in carotid and femoral arteries after a 5-year period using ultrasound in subjects with chronic hepatitis C and in controls matched for classic atherosclerotic risk factors. A total of 40 patients and 40 controls were assessed by echocolor Doppler in 2001 and in 2006 to evaluate plaque and intima-media thickness. The patients showed no changes in plaque and intima-media thickness during the 5-year period in all districts examined, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 10 publications
2
21
0
1
Order By: Relevance
“…However, HCV infection was no longer associated, after adjustment, with greater IMT, regardless of HIV status, compared with controls 16. Similarly, other reports in the setting of mono-infected patients,17 18 haemodialysis patients19 and HIV coinfected patients,20 found no association between HCV infection and vascular alterations.…”
Section: Evidence From Case Control Studiesmentioning
confidence: 66%
See 1 more Smart Citation
“…However, HCV infection was no longer associated, after adjustment, with greater IMT, regardless of HIV status, compared with controls 16. Similarly, other reports in the setting of mono-infected patients,17 18 haemodialysis patients19 and HIV coinfected patients,20 found no association between HCV infection and vascular alterations.…”
Section: Evidence From Case Control Studiesmentioning
confidence: 66%
“…Specifically, in a study of health in Pomerania (SHIP), hepatitis B surface antigen or anti-HCV positive patients, considered together, had a higher risk of both stroke and myocardial infarction prevalence compared with non-infected subjects, even if this association was not maintained after correction for metabolic confounders 18. Similarly, other population and case control studies assessing the association between markers of HCV infection and CAD24 or myocardial infarction17 25 26 reported no significant association.…”
Section: Evidence From Case Control Studiesmentioning
confidence: 99%
“…However, other reports did not find an excess significant risk [24][28]. Further, Bilora et al found that HCV infection delayed the process of atherosclerosis [29]. Differences in study design, patient source, case definition, and sample size may explain the observed variability discovered among studies.…”
Section: Introductionmentioning
confidence: 92%
“…In a conflicting report, Bilora et al 21 reported on a protective role of chronic viral hepatitis (B and C) on atherogenic plaque formation in the carotid, abdominal, and femoral regions. In this 5-year follow-up study, they observed a protective effect of HCV seropositivity and chronic HCV infection against carotid and femoral atherosclerosis.…”
Section: Hepatitis Virusesmentioning
confidence: 99%